2017
DOI: 10.2527/jas2016.1134
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, rumen fermentation, bacteria composition, and gene expressions involved in intracellular pH regulation of rumen epithelium in finishing Hu lambs differing in residual feed intake phenotype

Abstract: The objective of this study was to evaluate the effect of residual feed intake (RFI) on rumen function in finishing lambs. A total of 60 male Hu lambs (average initial BW = 25.2 ± 2.5kg) were used and were offered a pelleted high-concentrate diet, of which the forage to concentrate ratio was 25:75. Individual feed intake was recorded over a period of 42 d, then 10 lambs with the lowest RFI and the highest RFI were selected, respectively. The rumen fluid used for fermentation variables and relative abundance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
7
0
8
Order By: Relevance
“…At the end of the fattening period, ruminal fluids were obtained 2-4 h after the morning feeding, from five lambs randomly selected from each treatment, using an orogastric tube [17] Ruminal fluid pH was measured immediately after sampling using a portable pH meter (PHB-4, Shanghai, China). Ruminal fluid samples were strained through four layers of cheesecloth, and samples of 10 mL of filtrate were preserved with 1 mL of 25% metaphosphoric acid, stored at -20 • C for volatile fatty acids (VFA) determination [18].…”
Section: Ruminal Fermentation Parametersmentioning
confidence: 99%
“…At the end of the fattening period, ruminal fluids were obtained 2-4 h after the morning feeding, from five lambs randomly selected from each treatment, using an orogastric tube [17] Ruminal fluid pH was measured immediately after sampling using a portable pH meter (PHB-4, Shanghai, China). Ruminal fluid samples were strained through four layers of cheesecloth, and samples of 10 mL of filtrate were preserved with 1 mL of 25% metaphosphoric acid, stored at -20 • C for volatile fatty acids (VFA) determination [18].…”
Section: Ruminal Fermentation Parametersmentioning
confidence: 99%
“…Those data suggested that, compared with L-eff cattle, changes in ruminal bacteria in M-eff cattle might contribute, at least in part, to better rates of digestibility of dry matter, organic matter, and neutral detergent fiber [9]. Other studies detected greater concentrations of energy-related metabolites in the rumen of M-eff lambs and dairy cows including butyrate and propionate [10,11], suggesting a contribution of these microbial-derived compounds to energy metabolism and milk production [12]. Unlike mature ruminants, neonatal calves have an undeveloped rumen until close to weaning.…”
Section: Introductionmentioning
confidence: 95%
“…Dietary nutrients are fermented by rumen rumen microbial, such as bacteria, fungi and protozoa, and then degraded into VFA and MCP to provide energy for ruminants [51] and to guarantee the healthy and stable rumen environment [52,53]. In such reactions, rumen pH plays a decisive role in the composition and abundance of rumen micro ora, and is an important indicator re ecting whether the composition and abundance of rumen micro ora are normal [54,55]. Similarly, rumen microbial is also in uenced by animal species, diet composition and different ages [56][57][58].…”
Section: Discussionmentioning
confidence: 99%